Pengawetan dengan Asam Sitrat Ekstrak Daun Jeruk Purut (Citrus hystrix D. C) untuk Memperbaiki Umur Simpan Daging Ayam Segar - Jantri Nyama Yanti; Muryoto Muryoto; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2013)
Chicken meat is one of perishable foods because of its high protein and water content. There-fore, the addition of food preserving ingredient to extend the preservation time become frequent. In this context, the use of natural ingredient is more advised, one of which is the leaves of citrus hystric or jeruk purut (indonesian). The study was aimed to understand the effect of the addition of different various dose of citric acid which is extracted from citrus hystric leaves towards the preserving time of fresh chicken/broiler meat by conducting an experiment which employed post test only with control group design. The preserving time were determined based on the organo-leptic score gained from color, odor and texture changing observed by ten housewives who were assigned as the panelists. The observation were conducted in three replications. The results showed that the preserving time yielded among the three dose variation of citric acid, i.e. 2 %, 4 % and 6 % were significantly different, and the 2 % dose was the best in improving the preser-ving time, i.e. 15,33 hours in average, compared with only 6,83 hours obtained from the control chicken meat.